Frequency dependent electrocaloric effect in Nb-doped PZST relaxor thin film with the coexistence of tetragonal antiferroelectric and rhombohedral ferroelectric phases. Issue 4 (March 2020) - Peng, Biaolin; Zhang, Miaomiao; Tang, Silin; Jiang, Jintao; Zhao, Wenguang; Zou, Bingsuo; Luo, Nengneng; Zhang, Qi; Leighton, Glenn J.T.; Shaw, Christopher; Liu, Laijun; Sun, Wenhong
Abstract: Electrocaloric refrigeration material with good comprehensive performance such as large temperature change ( ΔT ), coefficient of performance ( COP ) and electrocaloric coefficient ( ΔT/ΔE ), is very attractive in the design of commercial refrigeration devices. Here, a large positive ( ΔT ∼ 12.3 K with ΔS ∼ 13.6 J K −1 kg −1 at 293 K) at 10 kHz and negative EC effects ( ΔT ∼ - 5.8 K with ΔS ∼ - 4.5 J K −1 kg −1 at ∼ 425 K) at 100 Hz are obtained in the Nb-doped Pb0.99 (Zr0.65 Sn0.3 Ti0.05 )0.98 O3 antiferroelectric thin film by using a sol-gel route. Moreover, the large positive and negative EC effects are sensitive and dependent to the applied frequencies. As the applied frequency increases, the positive EC effect intends to increase. However, the negative EC effect intends to decrease as the applied frequency increases. This interesting phenomenon is ascribed to the co-coupling between the phase-transition (nanoscale tetragonal transferring into rhombohedral along the direction which is vertical to the surface of the thin film, namely the [111]) & defect dipoles. Moreover, the COP (3.37) and ΔT/ΔE (0.01 K⋅cmkV −1 ) are also comparable to those of previous research works. These breakthroughs and findings enable the Nb-doped PZST thin film an ideal candidate for application of next-generation solid-state cooling devices.